Establishing Knowledge Centers: Applying The CIPPO Evaluation Model to Enhance The Efficiency of Libraries at Islamic Schools - Meri Sasdi; Sudarwan Danim (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The library plays a crucial role as the nucleus of academic knowledge and necessitates efficient management for the learning process. This study aims to assess how legal principles are implemented as guidelines for the structure and administration of school libraries, particularly within the Al-Hasanah Foundation. This evaluation is based on compliance with Regulation Number 12 of 2017, issued by the Head of the National Library of the Republic of Indonesia, delineating national library standards. Employing a qualitative and evaluative research approach, this study applies the CIPPO assessment model to monitor and evaluate the operational features of the library. Evidence suggests that the Al-Hasanah Foundation Library needs to adequately meet the predetermined criteria due to a shortage of personnel, resulting in inefficiencies in executing duties, providing services, and implementing school library initiatives. Despite these challenges, the Al-Hasanah Foundation Library effectively addresses the information needs of its users, especially in acquiring library resources. The highlighted constraints significantly impact visitor engagement, underscoring the necessity of resolving human resource limitations to enhance library performance.